THE EFFECT OF HEALTH EDUCATION IN DIABETIC MELLITUS ON KNOWLEDGE LEVEL USING LEAFLET IN LAUT DENDANG VILLAGE - Tambunan, Dior Manta; Silaen, Harsudianto; Tambun, Yetty Mariani (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
Blood glucose levels rise in diabetic mellitus (DM), a metabolic disorder that is not communicable. The cause is impaired insulin function and abnormal insulin secretion. Diabetes mellitus causes various complications. One way to prevent and overcome these complications is through health education. This study sought to determine whether health education about diabetes mellitus had an impact on Laut Dendang Village residents' level of knowledge. This kind of study is quantitative pre-experimental and uses a total sampling technique with a pre-experimental pre-posttest design with one group without control and the number of respondents were 30 people. Evaluation of knowledge scores was measured using the Diabetic Knowledge Questionnaire (DKQ-24) with 24 question items. Data analysis used the Wilcoxon test. The results of the study used wilcoxon test that there was effect of health education in diabetic mellitus management on knowledge level in Laut Dendang Village with p-value = 0.001 (? < 0.05). It is suggested for future research to add variables of Medication Compliance, Medication Supervisor, Family Support, Quality of life and Health Locus of Control.